Finance-dominated capitalism in crisis: The case for a Global Keynesian New Deal - Eckhard Hein; Achim Truger (Hochschule für Wirtschaft und Recht Berlin, Institute for International Political Economy (IPE), 2010)
We analyse the long-run imbalances of finance-dominated capitalism underlying the present crisis - which began in 2007 - with a focus on developments in the US and Germany. We argue that beyond inefficient regulation of the financial sector, the severeness of the present crisis has been mainly caused by increasing inequalities of income distribution and rising imbalances in the world economy associated with finance-dominated capitalism. From this it follows that in the near and not so near future, the US will no longer be able to act as the driving force for world demand. In order to avoid a period of deflationary stagnation in major parts of the world economy, we finally propose the policy package of a Global Keynesian New Deal which should consist of: 1. re-regulation of the financial sector, 2. re-orientation of macroeconomic policies along (Post-)Keynesian lines, and 3. re-construction of international macroeconomic policy coordination, in particular on the European level, and a new world financial order.
Keywords: E32; E44; E61; E63; E65; 330; Finance-dominated capitalism; financial crisis; macroeconomic policies; Global Keynesian New Deal